1991
DOI: 10.1007/bf00015002
|View full text |Cite
|
Sign up to set email alerts
|

Settling flux and sinking velocity of Seston in Lago di Mergozzo (Northern Italy) and influence of microbial activity on the decomposition of entrapped organic material

Abstract: Settling flux and velocity of seston, Particulate Organic Carbon (POC) and chlorophyll a were measured at three depths during 8 seven-day exposure periods in Lago di Mergozzo (Northern Italy). Sedimentation rates of seston varied from 250 to 1200 mg me2 d-' with a prevalence of the inorganic fraction (130-900mgm-2d-1) over the organic (160-320mgm-2d-'). The percentage of organic fraction inside the traps was always lower than outside. The comparison of preserved and unpreserved traps showed no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
5
0
3
Order By: Relevance
“…pers.). The mean sedimentation rate of chlorophyll a (5.8 mg m -2 day -1 ) was in the same order of magnitude as that reported by CALLIERI et al (1991). The sedimentation rates of metals are presented in Tab.…”
Section: Resultssupporting
confidence: 81%
“…pers.). The mean sedimentation rate of chlorophyll a (5.8 mg m -2 day -1 ) was in the same order of magnitude as that reported by CALLIERI et al (1991). The sedimentation rates of metals are presented in Tab.…”
Section: Resultssupporting
confidence: 81%
“…The organic C fluxes in the post-closure interval exceed most values reported for other eutrophic lakes, including Rotsee (49), Frains Lake (50), Third Sister (50), Lake Lugano (66), Lake Hallwil (67), Lake Zug (2), and Lake Sempack (12). The only two exceptions (68,69) (2,7,70). The high settling velocity for Onondaga Lake is consistent with the unusually high Ca 2+ concentrations that continue to prevail (Figure 1b) and the coagulation mechanism for enhanced deposition.…”
Section: Resultsmentioning
confidence: 82%
“…The question now is why after thermocline establishment, particles flux decreases, if several authors have found that stratification processes accelerating sedimentation and total fluxes of sestonic material? (Karl et al, 1988;Galvez et al, 1989;Callieri et al, 1991;Alvarez-Cobelas et al, 1993;Maricato, 1994;Wetzel, 2001). As has been raised previously, the sestonic material collected in traps is mainly allochthonous, and this depends on the loads entering the reservoir by the three tributaries and of the period of greatest stratification.…”
Section: Discussionmentioning
confidence: 99%
“…In the water from each tube it was measured TS, TSF, TVS, TDS, TSS, TVS and TSF by gravimeter (APHA, 1995); and electrical conductivity, turbidity, pH, dissolved inorganic carbon (DIC) (Mackereth et al, 1972). The sedimentation rate (flux) g m -2 d -1 was established only for the TS, TSS, TVS and TSF and was calculated according to the Equation 1 in Callieri et al (1991):…”
Section: Introductionmentioning
confidence: 99%